2018
DOI: 10.1128/jvi.01972-17
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of the Cytoplasmic Domain of Influenza A Virus M2 Protein Is Crucial for Production of Infectious Virus Particles

Abstract: Virus replication is mediated by interactions between the virus and host. Here, we demonstrate that influenza A virus membrane protein 2 (M2) can be ubiquitinated. The lysine residue at position 78, which is located in the cytoplasmic domain of M2, is essential for M2 ubiquitination. An M2-K78R (Lys78→Arg78) mutant, which produces ubiquitination-deficient M2, showed a severe defect in the production of infectious virus particles. M2-K78R mutant progeny contained more hemagglutinin (HA) proteins, less viral RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 45 publications
0
30
1
Order By: Relevance
“…Additional viral components outside of the replication complex have shown a requirement for ubiquitination that can directly impact viral propagation. Identification of K78 on the cytoplasmic domain of the IAV M2 protein as a target for ubiquitination uncovered a role for ubiquitin in the successful formation of progeny virions [195]. Mutant viruses harbouring a K78R switch in their M2 protein produced severely flawed viral particles that lacked vRNA and vRNPs and otherwise appeared empty under electron microscopy observation [195].…”
Section: Novel Pro-viral Roles Of Trims and Other E3 Ubiquitin Ligasesmentioning
confidence: 99%
“…Additional viral components outside of the replication complex have shown a requirement for ubiquitination that can directly impact viral propagation. Identification of K78 on the cytoplasmic domain of the IAV M2 protein as a target for ubiquitination uncovered a role for ubiquitin in the successful formation of progeny virions [195]. Mutant viruses harbouring a K78R switch in their M2 protein produced severely flawed viral particles that lacked vRNA and vRNPs and otherwise appeared empty under electron microscopy observation [195].…”
Section: Novel Pro-viral Roles Of Trims and Other E3 Ubiquitin Ligasesmentioning
confidence: 99%
“…To date, many viral proteins have been reported to be ubiquitinated, including influenza A virus-encoded NP, M2 and PB1 [25][26][27][28], Dengue Virus-encoded NP [29], and 54 viral proteins encoded by the wellcharacterised cowpox virus strain [30]. In ubiquitinated proteins, Ub is frequently found to be covalently conjugated to Lys residues, but non-Lys residues of substrates such as serine (Ser), threonine (Thr) and cysteine (Cys) are also modified in rare cases.…”
Section: Identification Of Viral Proteins Modified By Ubiquitinationmentioning
confidence: 99%
“…For example, BPLF1 of three DUBs encoded by EBV genome was reported to contributes to innate immune evasion through interference with toll-like receptor signalling [56], and arterivirus papain-like protease 2 with the activity of DUB can suppresses the innate immune response in infected host cells [57]. Moreover, NP, M2 and PB1 proteins of influenza A virus are ubiquitinated, and this affects replication of the viral genome [25][26][27][28]. Furthermore, Kirui et al revealed that ubiquitination can up-regulate influenza virus polymerase activity, directly enhancing viral RNA synthesis [58].…”
Section: Viruses Manipulate the Ups To Favour Viral Propagationmentioning
confidence: 99%
“…Post-translational modification is important for protein function, stability, cellular localization, and protein-protein interactions. Recent studies have shown that posttranslational modifications of viral proteins modulate the virus life cycle, e.g., phosphorylation of influenza viral proteins (NS1, M1, and NP) plays important roles in virus replication [35][36][37][38]. The ubiquitination of NP and M2 proteins is crucial for viral RNA replication and the production of infectious virus particles [37].…”
Section: Discussionmentioning
confidence: 99%